IMPLICATIONS OF FIXED ASSET REVALUATION ON FINANCIAL STATEMENT PERFORMANCE AND COMPANY CAPITAL STRUCTURE: A CASE STUDY OF PT. LUMBUNG PEDIA KERAMIK - Resmina, Herty Widyatini; Zaman, Komarun; PRATAMA, DEVANGGA; Nuryadi (Sekolah tinggi ilmu ekonomi pemuda, 2025)
Historical valuation of fixed assets often does not reflect the current fair value, so revaluation is one of the accounting policies that can measure this gap. This study aims to analyze the effectiveness of fixed asset revaluation on the company's financial statement performance and capital structure, through a case study at PT. Lumbung Pedia Keramik. The variables used include Debt to Equity Ratio (DER), Fixed Assets to Net Worth, and Return on Investment (ROI). The analysis method is a normality test followed by a Paired Sample t-Test to compare the ratios before and after the revaluation. The results of the study stated that fixed asset revaluation did not provide a significant difference in the three ratios. The implication of this finding is that although revaluation increases the book value of assets, its direct effect on financial performance and capital structure is not automatically significant. This study suggests that companies carefully consider the costs and benefits of revaluation before its implementation